Struggle Over Utah's San Rafael Swell : Wilderness, National Conservation Areas, and National Monuments - Durrant, Jeffrey O., 1966- (Book collections on Project MUSE., 2007)
The sandstone crags and twisting valleys of the San Rafael Swell present a formidable landscape, but as this book clearly shows, the political landscape may be even more daunting, strewn with bureaucratic boulders and embedded with fixed positions on the functions and values of public land.